Biological behavior of the gerbil ventral prostate in three phases of postnatal development - De Campos, SGP (2006)
In this study, we characterized the gerbil's ventral prostate histology ultrastructurally and quantitatively throughout three phases of postnatal development (young, adult, and old) in order to comprehend its biological behavior and propensity to developing spontaneous lesions with aging. The gerbil prostate is composed of alveoli and ducts immersed in a stroma composed of smooth muscle, fibroblasts, collagen and elastic fibers and vessels. The prostate tissue components present morphological and quantitative aspects that vary according to age. Young animals have an immature gland with modest secretory activity. Synthetic activity remained stable in adult and old gerbil. However, prostatic morphology was altered in the aging, showing an increased epithelium and stromal fibrosis. The nuclei of the secretory cells increased with aging, whereas nucleoli presented few alterations during postnatal development. The epithelial proliferation and stromal remodeling noted in this study indicate that the gerbil prostate may respond to the androgen declines typical of senescence through epithelial proliferation and stromal remodeling.